PENGUKURAN KINERJA KEUANGAN PERUSAHAAN DENGAN METODE ANALISA CASH FLOW RATIO - Nurul Latifah Pancawardani (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2009)
This paper will describe in a normative doctrinaire one alternative method performance measuring company is Cash flow Ratio Analysis . Attention with this Cash flow is very important because  the company in this operational have to attention talent to complete cash from the external of it. Cash flow is process in the inside there’s enter out Cash flow and in Cash flow effect of company operation. The company activities with Cash flow : 1) Cash flow from operating (CFFO) activities, 2) Cash flow from investing activities, 3) Cash flow from financing activities .